Effect of mechanical fatigue on the bond between zirconia and composite cement - Vidotti, Hugo Alberto; Carvalho, Ricardo M.; Coelho, Paulo G.; Zambuzzi, Willian F. [UNESP]; Bonfante, Gerson; do Valle, Accácio L.; Bonfante, Estevam A. (My University, 2017)
Purpose: To examine the effect of mechanical fatigue on the bond strength of resin composite cemented to silicacoated yttria-tetragonal zirconia polycrystal ceramic (Y-TZP). Materials and Methods: Ten Y-TZP blocks were polished down to 600-grit silicon carbide paper. Specimens were silica coated by airborne-particle abrasion with 30-μm silica-modified Al2O3 particles. Blocks were cleaned in an ultrasonic bath, and a dental adhesive was applied and light cured for 20 s. Pre-cured composite blocks were luted to treated Y-TZP surfaces with a dual-curing resin cement. Half of the samples (n = 5) were subjected to mechanical fatigue before trimming (fatigue group) and the other half tested 24 h after bonding procedures (control group). Fortyfive beam-shaped samples with an approximately 1 mm2 cross-sectional area were prepared for each group and tested in microtensile mode at 0.5 mm/min. Fractographic analysis was performed by optical and scanning electron microscopy. Only specimens that failed at the interface area were considered for statistical analysis. Weibull distribution (95% confidence bounds) was used to determine the characteristic strength (σ0 in MPa) and Weibull modulus (m) for each group. Probability of survival was calculated over the range of loads until specimens failed. Results: The control group showed σ0 = 45.91 MPa and m = 7.98, and the fatigue group σ0 = 43.94 MPa and m = 6.44 (p > 0.05). The probability of survival did not differ significantly between groups. Conclusions: Fatigue did not affect the bond strength between silica-treated Y-TZP intaglio surfaces and composite cement under these experimental conditions.
Keywords: Mechanical fatigue; Microtensile bond strength; Silica coating; Weibull; Zirconia